Empowerment of women households group of poor families to increase income through training to make dimsum in Padang Bulan Village, Medan - Siregar, Onan M; Thamrin, Husni; Ridho, Hatta; Arifin, Adil (Talenta Publisher, 2021)
Community service activities are carried out through training on how to make dim sum which is carried out for mothers from poor family groups located in Padang Bulan Village, Medan City. Based on data and observations that mothers from poor groups who do not have a job other than taking care of their family, the purpose of this service is to provide training to mothers from poor family groups to make decent dim sum for sale so that they can increase family income. The method in this activity is carried out by socializing and giving lectures to training participants as well as doing hands-on practice on how to make dough for dim sum ingredients and form dim sum properly to sell to consumers. Through the dim sum-making training activities, mothers from poor family groups will become skilled and have the expertise to make and sell dim sum to the community which in turn will increase family income.